Brain Tumor Detection Using Cnn (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Artificial Intelligence has greatly benefited the medical field. One of its many diverse applications includes the use of AI in diagnosis to minimize the error due to human judgment. There are a variety of imaging techniques that are being used in recent times that include Computed Tomography Scan (CT), Magnetic Resonance Imaging (MRI), etc., MRI is one the most reliable techniques owing to its reliability and safety. This paper aims to present a similar technique wherein we propose to use a convolutional neural network to detect the presence of the tumor.